Evaluation of five preservation methods for recovery of DNA from bone. Issue 1 (December 2019) - Iyavoo, S.; Hadi, S.; Goodwin, W.
Abstract: The effectiveness of five methods for the preservation of bone were assessed: cell lysis solution (with 1% sodium azide), dehydration/freeze-drying, ethanol (96%), freezing, and room temperature storage. Preserved bone samples were extracted using five optimised extraction methods. These preservation methods were tested for their efficiency for storage of fresh and degraded bone samples for 6 weeks, 6 months and 1 year. Freezing was found to be the best preservation method for longer-term storage of bone samples; this was followed by ethanol (96%), dehydration/freeze-drying, and room temperature storage. Full profiles were obtained from bone samples using all these preservation methods.